2017
DOI: 10.18488/journal.8.2017.54.431.449
|View full text |Cite
|
Sign up to set email alerts
|

Title: Determinants of School Efficiencies from Innovative Teaching through Digital Mobile E-Learning for High Schools: Application of Bootstrap Truncated Regression Model

Abstract: Article HistoryThe goal of this research is to evaluate the innovative teaching to affect school efficiency through using digital mobile e-learning of high school in Taiwan. Based on data envelopment analysis (DEA) and bootstrap truncated regression (BTR) model. The empirical results of this research indicate the following results: (1) Importing digital mobile e-learning can really enhance the efficiency of school management. (2) The results suggested in BTR model justifies that among the eight-factor analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In the paper of Liu et al [13] indicated that uses the digital mobile e-learning can affect the school efficiency and the innovative of teaching in in Taiwan's high school. Their research used Tobit Regression Model (TRM) to find the determinants for affecting the efficiency of school management.…”
Section: Results Analyzementioning
confidence: 99%
See 1 more Smart Citation
“…In the paper of Liu et al [13] indicated that uses the digital mobile e-learning can affect the school efficiency and the innovative of teaching in in Taiwan's high school. Their research used Tobit Regression Model (TRM) to find the determinants for affecting the efficiency of school management.…”
Section: Results Analyzementioning
confidence: 99%
“…Therefore, this study employed quantitative results to analysis study approach to gain an in-depth and holistic understanding of digital mobile e-learning. Moreover, we also utilize the analysis results from two articles [13], [14] to analyze these factors which affecting the relative efficiencies of schools by utilizing related factors.…”
Section: Methodsmentioning
confidence: 99%
“…The ages were 8.4% ( 27) for those under 35 years old, 30.3% (98) for 45 years old, and 61.3% (198) for those over 46 years old. The highest level of educational attainment was 61.3% (198) for graduate students and higher, followed by university graduates at 30.3% (98) (Litimi, 2019); (Liu and Kuo, 2017).…”
Section: Demographic Characteristics Analysismentioning
confidence: 99%